1999
DOI: 10.1007/s11894-999-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

The ileal brake: A fifteen-year progress report

Abstract: The "ileal brake" is the primary inhibitory feedback mechanism to control transit of a meal through the gastrointestinal tract in order to optimize nutrient digestion and absorption. Neurohormonal factors mediating this response continue to be identified. Recently, additional brakes that fine-tune transit have been described. When gut traffic control is disrupted, pathologic states characterized by malabsorption and impaired drug bioavailability manifest as diarrhea and malnutrition. An understanding of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 40 publications
1
65
0
1
Order By: Relevance
“…8 These effects have been attributed to the activation of the ileal brake mechanism. 5 Until recently, it was assumed that undigested nutrients reach the distal small intestine only under conditions of malabsorption or maldigestion. A more recent study in dogs has clearly shown that even under physiological circumstances, unabsorbed fat reaches the distal small intestine and activates the ileal brake mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8 These effects have been attributed to the activation of the ileal brake mechanism. 5 Until recently, it was assumed that undigested nutrients reach the distal small intestine only under conditions of malabsorption or maldigestion. A more recent study in dogs has clearly shown that even under physiological circumstances, unabsorbed fat reaches the distal small intestine and activates the ileal brake mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] This may be achieved by activation of the ileal brake. 5 The ileal brake is the primary inhibitory distal-to-proximal feedback mechanism that controls meal transit through the gastrointestinal tract and is thought to regulate and optimize nutrient digestion and absorption. 5 Several studies have shown that direct delivery of lipids into the ileum delays gastric emptying, 6 prolongs small intestinal transit time 7 and induces satiety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixth, the lipids in the GI tract provoked delay in gastric emptying which resulted in increased residence time of the co-administered lipophilic drug in the small intestine. This enabled better dissolution of the drug at the absorptive site and thereby improved the absorption (Citters and Lin 1999).…”
Section: Discussionmentioning
confidence: 99%